Public-Private Partnerships for Sustainable and Equitable Transportation Infrastructure - Mohammad Wasil; Setiadi (Logistica : Journal of Logistic and Transportation, 2025)
This review examines the role of Public-Private Partnerships (PPPs) in advancing sustainable and equitable transportation infrastructure. The findings highlight that clear governance frameworks and transparent regulations are central to building investor confidence and ensuring project success. Effective risk management strategies, such as demand forecasting and Build-Operate-Transfer models, enhance financial viability, while social inclusion and environmental sustainability can be strengthened through community engagement and green technologies. However, persistent challenges in developing countries—weak institutions, regulatory inconsistency, and economic instability—limit effectiveness. This review contributes by synthesizing comparative insights across global contexts and emphasizing the systemic factors that shape PPP outcomes.